MO773: The Impact of the Time on Dialysis and Kidney Transplantation on Arterial Ultrasound Characteristics. (3rd May 2022) - Barata, Rui; Damas, Juliana; Assis Pereira, Tiago; Nolasco, Fernando
Abstract: BACKGROUND AND AIMS: Vascular accesses (VA) are essential for efficient haemodialysis and preoperative vascular mapping through ultrasound (US) may help surgical planning and improve its outcomes. Several factors can affect vascular quality, hampering the decision about which access to create and affecting VA patency and complications. Our study aims to identify the impact of time on dialysis and/or kidney transplantation in arterial US characteristics. METHOD: Retrospectively, we analysed a cohort of patients with chronic kidney disease in whom a US vascular mapping was performed for preoperative planning of dialysis access from 2018 to 2019. Besides demographical characteristics, patients were characterized regarding the presence of diabetes, hypertension, vascular disease (including coronary, cerebrovascular, or peripheral arterial disease), obesity and smoking (present or past). Vascular indicators were analysed by Doppler US of the arteries in both upper arms, particularly the radial and brachial arteries. Arterial indicators analysed included mean diameter and peak wave velocity (PWV), doppler waveform (mono, bi or triphasic) and calcification on both arms (on a score of 0 to 6). Patients were divided into three groups regarding whether they had not been transplanted and/or started dialysis (group 1), or if one or both conditions were positive for ˂ 5 years (group 2), or 5 or ≥years (group 3). Appropriate tests were applied recurring to SPSS v21.0. RESULTS: A total of 153 patients were included. The mean age was 64.54 ± 16 years, 80 (52.3%) were male, 124 (81.0%) were white, 27 (17.6%) were black and 2 (1.3%) were Asian. Most patients had hypertension (138, 90.2%), 70 (45.8%) had diabetes, 59 (38.6%) had arterial disease, 36 (23.5%) were smokers and 45 (29.4%) were obese. The majority of patients were attending for the first vascular access (102, 66.7%). Regarding time since dialysis and/or kidney transplant, most patients were on group 1 (91, 59.5%), 46 (30.1%) were on group 2 and 15 (9.8%) were on group 3. We found that there was a statistically significant correlation between the time since initiation of dialysis and/or kidney transplantation and radial and ulnar mean PWV (P-value 0.004 and 0.004, respectively), but not with their mean diameters. Moreover, this correlation was valid for radial mean PWV between patients on group 1 and group 3 (P-value 0.006, CI 95% 3.88–28.57), and for ulnar mean PWV between patients on group 1 and group 3 (P-value 0.003, CI 95% 6.06–34.69) and between group 2 and group 3 (P-value 0.022, CI 95% 2.02–32.45). No statistically significant correlation was found between the time since kidney transplantation and/or dialysis was started and vascular calcification. CONCLUSION: Our results show that patients who have been transplanted and/or started dialysis for 5 or more years (and, in the case of ulnar mean PWV, for ˂ 5 years too) have lower radial and ulnar mean PWV than patients who did not. Moreover, there is no statistically significant difference in radial and ulnar mean diameters and calcification between these groups. End-stage kidney disease (ESRD) is associated with peripheral arterial disease, which has a great impact on patients' morbidity and mortality and is mainly a manifestation of atherosclerosis. Besides the traditional risk factors, like hypertension or diabetes, some non-traditional risk factors contribute to the high prevalence of PAD in ESRD, like oxidative stress or uraemic retention solutes. Pathologically, this is usually associated with media thickness increase and media calcification. In this study, this phenomenon can be demonstrated by lower peripheral velocities, with less impact in calcification or arterial diameter. Furthermore, the arterial diameter should not be the sole US indicator when deciding which VA to create, especially in patients on dialysis or transplanted, since it does not reflect the changes in arterial flux that results from several cardiovascular changes.